2010
DOI: 10.1007/s12111-010-9130-5
|View full text |Cite
|
Sign up to set email alerts
|

Race, Wrongful Conviction & Exoneration

Abstract: Race, Wrongful Conviction & Exoneration is a sociological examination of the "sociology of punishment" that is a major problem in criminological research but almost entirely ignored by sociologists who study and research issues related to crime. We argue that although legal scholars have done the bulk of research on exoneration they have not addressed the relationship of race to exoneration. This paper examines the risk that race produces for wrongful conviction and ultimately for exoneration. Additionally, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…they reference the Winston-Salem community in North Carolina, as well as, the race relations in the state of Carolina, overall. Carolina is described as a dichotomy of 'whites as good and blacks as evil and repeated offenders' (Smith and Haggerty, 2011). Examined here are two cases of white individuals who deliberately murdered their family members and then blamed Black men for their crimes, who were subsequently convicted.…”
Section: Racial Tensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…they reference the Winston-Salem community in North Carolina, as well as, the race relations in the state of Carolina, overall. Carolina is described as a dichotomy of 'whites as good and blacks as evil and repeated offenders' (Smith and Haggerty, 2011). Examined here are two cases of white individuals who deliberately murdered their family members and then blamed Black men for their crimes, who were subsequently convicted.…”
Section: Racial Tensionsmentioning
confidence: 99%
“…In these communities, Black people are seen as "interchangeable", meaning once a Black individual is accused of a crime, law enforcement's focus is finding any Black man to arrest and convict. Whether they committed the crime or not is irrelevant (Smith and Haggerty, 2011). Therefore, it is clear that poor race relations in Carolina have resulted in numerous wrongful convictions by purposely blaming someone else.…”
Section: Racial Tensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies have examined the role of race in these areas of criminal processing, relatively little has been written about racial effects in patterns of wrongful conviction, likely because of persistent gaps in available data. The relevant studies have largely concluded that Blacks and Hispanics may be disproportionately at risk of wrongful conviction compared with Whites, and that these groups are overrepresented in available samples of exonerees (Bedau & Radelet, 1987;Garrett, 2011;Gross, Jacoby, Matheson, Montgomery, & Patil, 2005;Holmes, 2001;Huff et al, 1996a;Huff et al, 1996b;Parker et al, 2001;Scheck et al, 2003;E. Smith & Hattery, 2011;Taslitz, 2006).…”
Section: Non-legal Factors Related To Wrongful Convictionmentioning
confidence: 99%
“…The available literature generally indicates that racial disparities exist at all levels of the system that cannot be explained by racial group differences in offending parties (Alexander, 2012; Freiburger & Hilinski, 2010; Kansal, 2005; Liptak, 2008; Parker, Dewees, & Radelet, 2001; Phillips, 2008; G. D. Russell, 1994; E. Smith & Hattery, 2011; Steffensmeier, Ulmer, & Kramer, 1998; Street, 2001; Taslitz, 2006; Tellis, Rodriguez, & Spohn, 2010; Tonry, 2010; Zatz & Rodriguez, 2006).…”
Section: Prior Research On Wrongful Convictionmentioning
confidence: 99%